1993
DOI: 10.1113/jphysiol.1993.sp019927
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine‐activated potassium current in smooth muscle cells isolated from the pig coronary artery.

Abstract: SUMMARY1. The perforated patch technique with nystatin or amphotericin was used to record whole cell currents activated by adenosine in smooth muscle cells isolated enzymatically from pig coronary arteries.2. Adenosine (5-40 /SM) activated an outward current at a holding potential of 0 mV in 5 mm [K+]. and an inward current at -60 mV in 143 mm [K+] Openings became more frequent after the application of adenosine, with several levels then being detected. Openings of channels with a larger conductance were somet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
132
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(141 citation statements)
references
References 38 publications
8
132
1
Order By: Relevance
“…Similar to isoproterenol, adenosine is proposed to activate K ϩ channels via cAMP/ PKA-dependent phosphorylation or direct G-protein activation of the channel (9,33). However, the contribution of K V channels to adenosine or other cAMPmediated relaxation in isolated, intact arteries has not been reported previously.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to isoproterenol, adenosine is proposed to activate K ϩ channels via cAMP/ PKA-dependent phosphorylation or direct G-protein activation of the channel (9,33). However, the contribution of K V channels to adenosine or other cAMPmediated relaxation in isolated, intact arteries has not been reported previously.…”
Section: Discussionmentioning
confidence: 99%
“…This notion, however, does not unequivocally mean that any adenosine mediated relaxation is exerted through an action at the A 2 -receptor, as there are references describing A 1 -receptor mediated relaxations. Thus, in the adenosinemediated relaxation of the rat duodenum (Nicholls et al, 1992), in the pig coronary arteries (Merkel et al, 1992;Dart & Standen, 1993) and in rat diaphragmatic arterioles (Danialou et al, 1997), the involvement of both the A 1 -and A 2 -receptor subtypes has been suggested. In the present study, the contribution of the A 1 -receptor to pig intravesical ureter relaxation has been discarded because of the low potency shown by adenosine and CPA, as well as by the lack of e ect of 10 78 M DPCPX, a concentration selective for blocking the A 1 -receptor, on relaxations to adenosine and NECA.…”
Section: Discussionmentioning
confidence: 99%
“…adenosine or hypoxia in cells freshly isolated from the same tissue (35 pS, Dart & Standen, 1993;. In rabbit portal vein, the channel activated may have a slightly lower conductance of 26 pS (Kamouchi & Kitamura, 1994), though a higher conductance channel has also been reported to be activated by another K ATP channel opener, pinacidil, in this tissue (50 pS, Kajioka et al, 1991).…”
Section: K + Channel Activation By Nicorandilmentioning
confidence: 99%
“…The low level of background channel activity in arterial smooth muscle cells sometimes makes it possible to resolve single channel events in whole cell recordings (Dart & Standen, 1993;. We were able to use this approach to study the channels activated by nicorandil in mesenteric arterial cells.…”
Section: Single Channels Activated By Nicorandilmentioning
confidence: 99%